Pengaruh Keefektifan Pengendalian Intern Akuntansi Terhadap Pencegahan Kecurangan Di PT. Indone Kargo Ekspress - Suandi, Fenny; Zulkarnen, Zuliana (UNIVERSITAS DHARMAWANGSA, 2023)
The effectiveness of internal control is the success of management in achieving agency goals related to maintaining the reliability of presenting financial reports, operational efficiency and compliance with applicable laws and regulations. The formulation of the problem in this research is how the effectiveness of internal accounting controls influences fraud prevention. This research aims to determine the effect of the effectiveness of internal accounting controls on fraud prevention at PT. Indonesia Kargo Express. The population of this research are employees in 4 departments at PT. Indonesia Kargo Express. By using the purposive sampling method, a sample of 50 employees was obtained. This research uses quantitative methods with data collection techniques through interviews and questionnaires. The data analysis used in this research is classical assumption testing, multiple linear regression analysis, and partial hypothesis testing (t-test) using SPSS (Statistica Product and Service Solutions) software. The results of this research indicate that the variable effectiveness of internal accounting control is significantly positive and has an effect on preventing fraud at PT. Indonesia Kargo Express.Keyword: Effectiveness, Accounting Internal Control, Fraud Prevention